2011
DOI: 10.1021/ja1113003
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Multicomponent Reactions to Polymer Science: Passerini Reactions of Renewable Monomers

Abstract: Combination of the Passerini three component-reaction (3CR) and olefin metathesis led to the formation of poly[1-(alkyl carbamoyl)alkyl alkanoates], a new class of polyesters with amide moieties in their side chain, from renewable resources. Two different approaches were studied and compared to each other. First, monomers were synthesized by the Passerini-3CR and then polymerized via acyclic diene metathesis. Alternatively, bifunctional monomers were synthesized by self-metathesis and then polymerized by Passe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
298
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(302 citation statements)
references
References 10 publications
0
298
0
3
Order By: Relevance
“…Given the mild reaction conditions, atom-economy, and tolerance to many functional groups, the Passerini reaction has been widely used in organic synthesis and drug development. In contrast, for polymer synthesis, the reaction remained unexplored until 2011, when Meier's group [86] first showed that diverse monomers prepared by Passerini-3CR could be polymerized using acyclic diene metathesis (ADMET) polymerization. Furthermore, they demonstrated a novel Passerini polymerization method that involves the use of a dicarboxylic acid and dialdehyde in combination with structurally diverse isocyanides to directly form high Scheme 19 Synthesis of brush conjugated polymers via Bergman cyclization [74,75].…”
Section: Passerini-3cr Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the mild reaction conditions, atom-economy, and tolerance to many functional groups, the Passerini reaction has been widely used in organic synthesis and drug development. In contrast, for polymer synthesis, the reaction remained unexplored until 2011, when Meier's group [86] first showed that diverse monomers prepared by Passerini-3CR could be polymerized using acyclic diene metathesis (ADMET) polymerization. Furthermore, they demonstrated a novel Passerini polymerization method that involves the use of a dicarboxylic acid and dialdehyde in combination with structurally diverse isocyanides to directly form high Scheme 19 Synthesis of brush conjugated polymers via Bergman cyclization [74,75].…”
Section: Passerini-3cr Reactionmentioning
confidence: 99%
“…Synthetic strategy for Passerini polymerization via the AA/BB/C approach [86][87][88]. molecular weight polyesters (Scheme 21(a)) [86].…”
Section: Scheme 21mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of efficient methods for the synthesis of polymers with novel structures and unique properties is of great academic significance and industrial implication [1][2][3][4][5][6][7][8][9][10][11]. There are numerous synthetic strategies that can control the topological [12][13][14][15][16][17][18][19][20] and sequence structures of polymers [16,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Currently, such approaches are frequently used and extended, [9][10][11][12][13][14][15][16][17][18][19][20] for example by starting from an alcohol which is oxidized in situ to the aldehyde, [21] while in polymer science a combination of the Passerini reaction and olefin metathesis leads to the formation of a new class of polyesters, namely, the poly [1-(alkylcarbamoyl)alkylalkanoates]. [22] On the other hand, hydrogen cyanide, [23] methyl cyanide, [24] and ethynyl isocyanide [25] have been detected in the interstellar medium, and HNC was recently observed in the atmosphere of Titan. [26] However, even if this family of compounds is the subject of many articles every year, only alkyl and aryl derivatives are extensively investigated in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%